Pengaruh Fasilitas Wisata, Promosi, dan Harga Terhadap Minat Berkunjung Kembali Wisatawan (Studi Destinasi Wisata Taman Ghanjaran Trawas) - Irine Eka Buana Dewi; Hadi Purnomo (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
This research is motivated by a decrease in the number of visitors to Taman Ghanjaran Tourism. The purpose of this study is to determine the effect of tourist facilities, promotions, and prices on the interest of visiting tourists. The sub ject of this research is visitors to Ghanjaran Park. This type of research uses quantitative methods using prim ary data and secondary data. The sam pling technique used in this research is purposive sampling with a total sample of 100 respondents. Data collection techniques use a questionnaire that has b een tested for validity and reliab ility. The data analysis technique used is multiple linear regression analysis. The results of the study using the t-test showed that the tourist facilities variable affected the interest in visiting tourists, the promotion variable not affected the interest in visiting tourists, and the price variable affected the interest in visiting tourists. The joint results (f test) show that the variab les of tourist facilities, prom otions, and prices have a significant effect on the interest of visiting tourists.